STUDY OF THE UTILIZATION OF PALM OIL INDUSTRY LIQUID WASTE - An Nisa Fitria; Vandhie Satyawira Gunawan; Mardiah Mardiah (Universitas Lambung Mangkurat, 2021)
Palm oil is one of the plantation crops that have high economic value and is growing rapidly. The wider the area of oil palm plantations in Indonesia, the more palm oil mills will process palm fresh fruit marks and produce waste from processed palm oil, namely solid waste and liquid waste. Each tonne of fresh fruit bunches (FFB) processed at the plant will potentially leave waste of about 23% empty palm oil, 4% wet decanter solid, 6.5% shell, 13% fiber, and 50% liquid waste. This review will discuss the utilization of palm oil mill liquid waste (LCPKS) which is organic material that still contains many benefits such as nutrients, therefore the application of liquid waste is an effort to recycle some of the nutrients (recycling nutrients) which is followed by harvesting fresh fruit bunches (FFB) from oil palm so that it will reduce the cost of fertilization which is classified as very high for oil palm cultivation. During the processing of oil palm fruit into palm oil in the palm oil industry, the remaining process is obtained in the form of liquid waste. If done properly, the liquid waste of the palm oil industry is considerable potential and can increase the added value of waste itself.Keywords: liquid waste industry, palm oil, utilization